Are referrals to hospital from out-of-hours primary care associated with National Early Warning Scores?. Issue 5 (9th January 2020) - Finnikin, Samuel; Hayward, Gail; Wilson, Fay; Lasserson, Daniel
Abstract : Background: The National Early Warning Scores (NEWS) is used in various healthcare settings to augment clinical decision making, and there is growing interest in its application in primary care. This research aimed to determine the distribution of NEWS among patients in UK out-of-hours (OOH) general practice and explore the relationship between NEWS and referral of patients to hospital. Methods: A historical cohort study using routinely collected data from the Birmingham Out-of-hours general practice Research Database. This includes patients who attended a large out-of-hours general practice provider in the West Midlands, UK, between July 2013 and July 2018. All adults who were seen face to face who had a full set of physiological observations recorded were included. NEWS was calculated post hoc, and subsequent hospital referral was the outcome of interest. Results: A NEWS was calculated for 74 914 consultations. 46.9% of patients had a NEWS of 0, while 30.6% had a NEWS of 1. Patients were referred to hospital in 8.5% of all encounters. Only 6.9% (95% CI 6.3% to 7.5%) of the 6878 patients referred to hospital had a NEWS of ≥5. Of the 1509 patients with a NEWS ≥5, 68.6% (95%CI 66.2% to 70.9%) were not referred to hospital. When considering how NEWS was related to hospital referral, the area under the receiver operating characteristic (AUROC) for patients seen in their own home was 0.731 (95%CI 0.681 to 0.787). For patient seen in treatment centres, the AUROC was 0.589 (95% CI 0.582 to 0.596). Conclusions: Patients seen in out-of-hours general practice have low physiological acuity. Those referred to hospital have a slightly higher NEWS overall. NEWS is poorly associated with hospital referral, although the association is stronger for patients seen in at home compared with patients seen in treatment centres. Implementing NEWS-based referral from OOH general practice is likely to increase hospital admissions.